'I'm a kid from the Bronx': A reflection on the enduring contributions of Willis's cultural production perspective in Learning to Labour. (December 2018) - Nolan, Kathleen
In this essay, the author discusses the enduring significance of Paul Willis's theorizations of cultural production and social reproduction as delineated in his classic work, Learning to Labour (1977). She reflects on the ways Willis's theory informs her experiences as a high school teacher and, later, as an ethnographer examining school policing in the Bronx. The author uses data on her research participants' experiences of schooling, the police, and the labour market within the context of neoliberal capitalism, ghettoization, and the intensified use of police force to show how a cultural production lens can provide important insights into the collective and spatialized experience of racial and class oppression. Further, the author argues that despite intensified repression in schools attended by poor and working class students of colour in US ghettoized areas, the transformative impulses within non-conformity signal a cogent social critique and can become a springboard for political action.